Effect of Sulfentrazone Application Method and Time, on Weed Control and Phytotoxicity in Flue-Cured Tobacco - Mazarura , Upenyu (Asian Journal of Agriculture and Rural Development, 2013)
Over a period of three years sulfentrazone, alone and in combination with other herbicides, was evaluated for weed control efficacy under various methods application. The trials were done in granite sandy soils after three years of Chloris gayana cv Katambora at Kutsaga Research Station, Zimbabwe. The chemicals were sprayed using a knapsack or a tractor mounted boom. Incorporation after ridging was done with a gang tiller set for shallow incorporation while that before ridging was done using a disk also set for shallow incorporation. Comparisons were made between directed and broadcast sprays, incorporation and no incorporation, timing from before planting to 4 weeks after planting (WAP). Application before holing out (BHO) and after holing out (AHO) was also evaluated. In most cases sulfentrazone gave good to excellent control of all weeds and was comparable to Metolachlor in efficacy. In some cases grass control was somewhat variable but acceptable. With regard to time of application, Sulfentrazone gave better control of broadleaf and grass weeds when applied from 1 to 4 WAP. Yellow nutsedge control was excellent and unaffected by time of application. Weed dry matter was reduced significantly relative to the untreated control for the 1 to 4 WAP applications. There was no significant difference between incorporation and surface or between directed and broadcast applications. The over top (OT) and AHO consistently gave better control than BHO application.